2010
DOI: 10.1590/s1413-35552010000500014
|View full text |Cite
|
Sign up to set email alerts
|

Escala de Locus de controle da dor: adaptação e confiabilidade para idosos

Abstract: Background: Pain is considered a multidimensional experience and is very common in the elderly. The pain locus of control has become essential to understand how the perceptions, expectations and beliefs are related to individual behavior, attitudes, coping and adherence of the elderly with regards to the health conditions and with the proposed treatment. Studies focused on adaptation and reliability of instruments are necessary for health professionals. Objectives: The present study performed the cross-cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
7
0
4
Order By: Relevance
“…Pain was evaluated in a multidimensional manner according to the Geriatric Pain Measure-p (GPM-p), an instrument that has undergone cross-cultural adaptation for use in Brazil and has had its psychometric properties evaluated, meaning that it is considered reliable and valid for use among the elderly 8 . This instrument allows pain to be considered in accordance with its various dimensions: sensory-discriminative, motivational-affective and cognitive-evaluative.…”
Section: Methodsmentioning
confidence: 99%
“…Pain was evaluated in a multidimensional manner according to the Geriatric Pain Measure-p (GPM-p), an instrument that has undergone cross-cultural adaptation for use in Brazil and has had its psychometric properties evaluated, meaning that it is considered reliable and valid for use among the elderly 8 . This instrument allows pain to be considered in accordance with its various dimensions: sensory-discriminative, motivational-affective and cognitive-evaluative.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that Chance HLC is usually associated with worse indicators of health or disease, while an internal locus of control is associated with positive indicators of health and disease. 3,7,12,13,15,17,18,34,35,36 Thus, dental patients with these profiles are more likely to accept medical or dental approaches and advice, 6 and this correlation may be used strategically by health professionals. Though the results are promising, those involving the "pure internal," "pure powerful others," and "yea-sayer" profiles require a closer scrutiny.…”
Section: Discussionmentioning
confidence: 99%
“…5 The original version of this instrument is written in English and consists of 18 items with a 6-point Likert response format ranging from strongly disagree (1) to strongly agree (6). The Portuguese version of the instrument used in this study was published by Araújo et al 15 The conditionspecific locus of control used was individuals' pain experience.…”
Section: Multidimensional Health Locus Of Control -Form C (Mhlc-c) Scmentioning
confidence: 99%
See 2 more Smart Citations